Th2 cells and cytokine networks in allergic inflammation of the lung - Anthony J. Coyle; Shogo Tsuyuki (Mediators of Inflammation)
The cytokines released from Th2 and Th2-like cells are likely to be central to the pathophysiolgy of asthma and allergy, contributing to aberrant IgE production, eosinophilia and, perhaps, mucosal susceptibility to viral infection. IL-4 has emerged as a central target, not only for B cell IgE production, but also in the commitment of both CD4+ and CD8+ T cells to cells with Th2 effector function capable of secreting IL-5 resultlng in eosinophilic inflammation. In view of the central role of this cytokine and the evidence that glucocorticoids are unable to modify many IL-4 dependent effects, Th2 inhibitors may prove to be novel therapies for the treatment of bronchial asthma.